Hypoxia-Inducible Factor-1α Expression Predicts a Poor Response to Primary Chemoendocrine Therapy and Disease-Free Survival in Primary Human Breast Cancer - Daniele Generali; Alfredo Berruti; Maria Pia Brizzi; Leticia Campo; Simone Bonardi; Simon Wigfield; Alessandra Bersiga; Giovanni Allevi; Manuela Milani; Sergio Aguggini; Valeria Gandolfi; Luigi Dogliotti; et al. (2006)
Abstract Purpose: To investigate the relationship of hypoxia-inducible factor-1α (HIF-1α) tumor expression in predicting the response to epirubicin and disease-free survival (DFS) in patients with breast cancer enrolled in a single institution trial of primary anthracycline and tamoxifen therapy. Experimental Design: The expression of HIF-1α was assessed by immunohistochemistry in 187 patients with T2-4 N0-1 breast cancer enrolled in a randomized trial comparing four cycles of single agent epirubicin versus epirubicin + tamoxifen as primary systemic treatment. All patients postoperatively received four cycles of the four weekly i.v. CMF regimen (cyclophosphamide, methotrexate, and 5-fluorouracil). Patients with estrogen receptor (ER)-positive primary tumors also underwent 5 years of treatment with adjuvant tamoxifen. Carbonic anhydrase IX (CAIX) was also scored as a marker of HIF activity. Results: Overall response to therapy progressively decreased with increasing tumor HIF-1α (P < 0.05), and HIF-1α was an independent predictor of response (P < 0.048). HIF-1α expression was also associated with a significantly shorter DFS (P < 0.02) in all patients and in ER-positive but not in ER-negative patients. Furthermore, CAIX positivity conferred a significantly shorter DFS (P = 0.02) compared with CAIX-negative tumors in patients with HIF-1α-negative tumors. Conclusions: HIF-1α expression in patients with breast cancer is a marker of poor therapy response and outcome, especially in ER-positive patients. The combination of two hypoxia markers has greater utility than assessing just one, and patients with hypoxia markers in their tumors may be suitable for administration of drugs that reduce HIF-1α expression and increase oxygen delivery to the tumor bed before starting neoadjuvant therapies.